A model to include turbulence-turbulence interaction in the prediction of trailing edge far field noise for high angles of attack or slightly separated flow. (June 2019) - Hornung, Cordula; Lutz, Thorsten; Krämer, Ewald
Abstract: The most dominant noise source of modern wind turbines is considered to be trailing edge (TE) noise. TE noise increases with increasing angle of attack of the flow. For wind turbine development it is hence crucial to predict TE noise for high angles of attack up to slightly separated flow. It results from wall pressure fluctuations induced by turbulent vortices in the boundary layer. The source term for the pressure fluctuations consists of two terms, the interaction of the mean shear with the turbulence and the turbulence-turbulence interaction (TTI). TTI is neglected in the commonly used TE noise prediction model by Blake, resulting in a strong dependency of the model on the wall normal mean velocity gradient. With increasing angle of attack this wall normal gradient of the boundary layer diminishes. Hence the TTI of the source equation has to be taken into account in order to achieve reliable predictions towards higher angles of attack. Here a new simplified-analytical model including the TTI, based on the model deduction by Blake, is presented and compared to experimental data. It is found that the prediction quality for high angles of attack and slight TE separation can be improved with the new model. Highlights: An improved model for trailing edge noise prediction is proposed. The model includes a new model for the turbulence-turbulence interaction. The model deduction follows the way used for the TNO model. It shows better prediction quality for high angles of attack and slightly separated flow.